Unsteady slipstream of a train passing through a high-speed railway tunnel with a cave. Issue 4 (2nd December 2022) - Xiong, Xiaohui; Cong, Rilong; Li, Xiaobai; Geng, Yutang; Tang, Mingzan; Zhou, Shujun; Na, Yanling; Jiang, Chongxu
Abstract: The cave is of great importance for the storage of equipment and to avoid having workers in the tunnel, but it changes the tunnel section, leads to a change of slipstream and affects the safety of trains and workers. The Re-normalization group (RNG) k -ε turbulence method is used to investigate the slipstream induced by a single train passing through a double-track tunnel at 350 km/h. The slipstream in a tunnel with and without a cave is compared. The slipstream components in three directions are reported comprehensively. The results show that the existence of a cave changes the slipstream at the tail of the train. At measurement points before and after the train passes the cave, the intensity of the slipstream at the tail is mitigated; as the train passes the cave, the tail slipstream is enhanced to a certain extent. With increasing lateral distance, the peak value of the slipstream with a cave decreases faster than that without a cave. These findings suggest that the presence of a cave mitigates the slipstream intensity, but special attention should be paid to the design of ancillary facilities, especially their relative location.